The Effect Of Soil Treatment With Cow Manure Compost And Foliar Magnesium On Plant Growth Of Black Diyala Fig Ficus Carica L. Seedlings - Alkhafaji, Mohammed K.A.; Al- Abbassi, Ghaleb BA (South Eastern European Journal of Public Health, 2024)
The research was conducted at the research station affiliated with the Faculty of Agriculture / University of Kufa in the university city in the Najaf Governorate for the period from 1 March to 1 December 2023 to study the effect of organic fertilization with cow manure compost and foliar spraying with magnesium and their interactions on some vegetative traits of black Diyala fig seedlings. The foliar magnesium was used at four concentrations (0, 0.5, 1 or 1.5) gm L-1, and the ground addition of organic fertilizer (cow manure) was also applied at four levels (0, 5, 10 or 15) g pot-1, and their interactions. The results showed that black Diyala fig seedlings treated with cow manure compost recorded significant effect on the studied traits, as cow manure compost at 15 g pot-1 resulted in the highest increase of seedlings height 21.37 cm, stem diameter 2.07 mm, number of branches 3.30 seedling branch-1, number Leaves 10.03 leaf plant -1, and leaf area 2448.25 cm2 seedling-1. Spraying fig seedlings of the Black Diyala variety with magnesium at a concentration of 1.5 gm l-1 excelled in the amount of increase in seedling height 15.98 cm, stem diameter 1.82 mm, number of branches 3.23 seedling branch-1, and number of leaves. 10.36 plant leaves-1, average leaf area is 1899.50 cm2 seedling-1. However, best results were recorded in the interaction of foliar magnesium at 1.5 gm L-1 and organic fertilizer at 15 g pot-1 with significantly the highest increase in plant height 25.56 cm and stem diameter 2.28 mm, the number of branches is 5.28 branches, seedling-1, the number of leaves is 15.00 leaves-1, the average leaf area is 3030.00 cm2, seedling-1.